O tema do outro em "O ser e o nada" - Luiz Henrique Vieira de Magalhaes (1999)
In this work, we search to elucidate Jean-Paul Sartre's elaboration, concerning the issue of the Other, undertook in his main book UÊtre et le Néant. We aim to present a version of the original equation of the author, showing how, begining with an especific cogito - cogito elargi - it is possible to assure the existence of the other starting from my own existence. Thus, we mean to show how, in my being, I depend on the other's being, and vice-versa. Our project relied upon an exegetic approach of the viewed work, from its inicial formulation to the moment of the explanation of this cogito.